El Diseño Universal para el Aprendizaje en la Preparatoria - Gutiérrez Jaramillo, Emily Stefania (2025)
The present research, entitled Universal Design for Learning (UDL) in high school, aimed to analyze the impact and importance of working in schools to improve education through the principles of multiple forms of representation, multiple forms of engagement, and providing ways of action and expression. This seeks to address diversity in the classroom, where teachers ensure educational inclusion regardless of learning styles, contexts, or disabilities, and that all students have equal access. The research included a theoretical framework with relevant and up-to-date research, detailed the variables mentioned, verified the qualitative methodology, and used a non-experimental design that was basic, bibliographic, field-based, descriptive, and cross-sectional in nature. The sample consisted of two high school teachers from the Fe y Alegría Basic Education School. The technique used in the research was the interview, using a questionnaire as an instrument. After its application, the results were interpreted. Finally, the conclusions and recommendations are presented, focusing on the level of knowledge that teachers use in their daily practice within the teaching-learning process with their students.